P-D8 Targeting of the catalytic site of host mTOR controls HIV in vivo. (January 2016) - Heredia, Alonso; Le, Nhut; Gartenhaus, Ronald; Sausville, Edward; Medina-Moreno, Sandra; Zapata, Juan; Davis, Charles; Gallo, Robert; Redfield, Robert
Abstract : HIV necessitates host factors for successful completion of its life cycle. Mammalian target of rapamycin (mTOR) is a conserved serine/threonine kinase that forms two complexes, mTORC1 and mTORC2. Rapamycin is an allosteric inhibitor of mTOR that selectively inhibits mTORC1. Rapamycin interferes with viral entry of CCR5 (R5)-tropic HIV and with basal transcription of the HIV LTR, potently inhibiting replication of R5 HIV but not CXCR4 (X4)-tropic HIV in primary cells. The newly developed ATP-competitive mTOR kinase inhibitors (TOR-KIs) inhibit both mTORC1 and mTORC2. Using INK128 as a prototype TOR-KI, we demonstrate potent inhibition of both R5 and X4 HIV in primary lymphocytes EC50 2 log10 units and partially restored CD4/CD8 cell ratios. Targeting of cellular mTOR with INK128 (and perhaps others TOR-KIs) provides a potential strategy to inhibit HIV, especially in patients with drug resistant HIV strains.